Voting interest and the party manifesto in 2019 presidential election in Nigeria - Ibrahim, Bashir (2020)
It is central within the domain of many literature concerning election in most of the developing democracies that the political parties ‘officials, candidates as well as their members did not see party‘s manifesto as an effective instrument for attracting the voting interest of the electorate. Thus, they employ to the large possible extent non issues based campaign factors to canvass for votes, even thought that the 2010 electoral law(as amended) made it categorically clear that the campaign should be based on party manifesto. This paper seeks to explain the centrality of party manifesto or otherwise in determining the voting interest of the electorate. The total numbers of voters that casted their votes during the conduct of 2015 general election in Bomo ward Sabon-Gari Local government Area of Kaduna State constituted the population of the study in which the multi-sampling stages was adopted for the questionnaire administration in order to ensure every segment of Bomo diverse population has been included in the sampling population. It was found that voters do not have adequate knowledge of the party manifesto of their voting interest which gave rise to the party manifesto to remain insignificant in determining of voters behaviours during the conduct of 2019 presidential poll in Nigeria. For this reason however, it should be one of the viable options for democracy and good governance in Nigeria the effective voters’ education to be taken into cognizance by all electoral stakeholders the party manifesto of registered political parties by all electoral stakeholders.